Strategi Komunikasi Dinas Pariwisata Dalam Melakukan Promosi Di Kota Medan - Muhammad Rahmat Hidayat; Sori Monang (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This article aims to find out the communication strategy of the Medan City Tourism Office. During the current pandemic, the tourism sector experienced a significant decline in tourists. Ironically, some tourist attractions were closed to prevent the spread of the virus. In the new normal era, tourism is currently trying to recover the number of tourists. This study uses a library approach. Data was collected through media analysis and observation. The results of the study show that the strategy implemented on the Medan City Tourism Office's social media is tourism content, events, business and organizational structure. This strategy is considered not very effective because there is no massive tourist growth yet.